A Edukasi Loving Baby Massage Pada Ibu Balita di Desa Siame : Edukasi Loving Baby Massage Pada Ibu Balita di Desa Siame - Sitti Fatimah; Muchtar, Asrianti Safitri; musni; Ita Novianti; Desi Heriyana (Lontara Abdimas : Jurnal Pengabdian Kepada Masyarakat, 2025)
Loving baby massage is a form of kinesthetic touch stimulation, verbal communication, and expression of parental affection for their babies. Baby massage itself is an effort to increase the baby's immunity so as to reduce the morbidity and even mortality rates of infants and toddlers. This activity aims to increase the knowledge of mothers of toddlers in Siame village regarding the importance of giving baby love massage to babies for growth and development. The final result obtained was that there was an increase in the knowledge of mothers who attended the Baby Love Massage counseling, which previously had good knowledge of 2 people (20%) and after being given Baby Love Massage Counseling increased to 7 people (70%). Counseling activities can increase public knowledge, especially mothers, regarding the importance of baby love massage which can be beneficial for baby growth and development.K